Body Mass Increase Induced by Eight Years of Artificial Selection in the Yellow Mealworm (Coleoptera: Tenebrionidae) and Life History Trade-offs. Issue 2 (7th March 2019) - Morales-Ramos, Juan A; Kelstrup, Hans C; Rojas, M Guadalupe; Emery, Virginia
Abstract: Efforts to improve rearing conditions of Tenebrio molitor L. (Coleoptera: Tenebrionidae) for insect biomass production included selecting for larger size pupae. The effects of an 8-yr continuous selection of T. molitor pupae for larger size were studied. Data consisting of daily counts and weights of pupae were analyzed using regression to determine the effects of selection over time. A preliminary evaluation of food conversion, growth, fecundity, and larval survival was done to compare ancestral versus selected strains. A significant positive correlation was identified between pupal size and time indicating a significant increase in pupal size over time in the selected T. molitor strain. A preliminary comparison of ancestral and selected strains showed significantly larger pupal size, growth rate, fecundity, and efficiency of conversion of ingested food in the selected strain. However, the selected strain also showed significantly lower larval survival than the ancestral strain. The low larval survival impacted the overall productivity of the selected strain resulting in no significant differences in biomass production when compared with the ancestral strain. The potential of using selection to improve biomass productivity in T. molitor is discussed.